New host record of Sclerotium rolfsii causing crown and root rot on Pseudogynoxis benthamii - Rivera, Marta Carolina; Wright, Eduardo Roberto; Silvestro, Luciana Belén; Steinglein, Sebastián Alberto; Kato, Adriana Elena (Instituto de Biología, Universidad Nacional Autónoma de México, 2022)
Symptoms of a wilt disease were observed on 10 of 40 plants of Pseudogynoxis benthamii grown in Buenos Aires, Argentina, in March 2016. The aim of this study was to identify the causal agent of the disease. Five phenotypically identical fungal isolates were obtained from sclerotia that developed on the roots of wilted plants. One of them was inoculated onto healthy plants, and caused symptoms in 2 weeks. The pathogen was identified as Sclerotium rolfsii, on the basis of morphological characteristics. The nuclear ribosomal DNA internal transcribed spacer region of the isolate was PCR-amplified and sequenced. DNA analysis revealed a 99-100% similarity with S. rolfsii. This is the first report of S. rolfsii causing wilt on P. benthamii and the first pathogen reported on this plant species worldwide.